The Effectiveness of the Program Keluarga Harapan (PKH) to Improve Community Welfare in Makmur Village, Palolo District, Sigi Regency - Nasnianti Pasangka; Rita Yunus; Edhi Taqwa; Failur Rahman; Mukhtar Tallesang (Manunggal Halim Jaya, 2024)
The purpose of this study was to determine how Program Keluarga Harapan (PKH) is implemented, how effective PKH is, and how well the PKH recipient community is. This study involved PKH Companions and PKH Recipients from Makmur Village, Palolo District. Research data were obtained through observation, interviews, and documentation. Then, the data was reduced, presented, and conclusions were drawn. The results of this study indicate that 1) Program Keluarga Harapan in Makmur Village has been implemented in accordance with the steps set for its implementation. 2) Program Keluarga Harapan has four indicators to measure its effectiveness, namely: program objectives, target setting, program socialization, and monitoring. Because the community receiving PKH assistance has met these four indicators, this program can be considered effective. 3) With PKH assistance, education, health, and daily needs have been met. Because it can help the community in meeting the needs of school children such as buying school clothes, toddler health, and daily needs, but there are still some PKH recipients who say that they do not feel better because they have just received PKH.